Development of a Clothing Sizing System for Benghazian Children Based on Anthropometric Measurements (The International Journal of Engineering & Information Technology (IJEIT), 2024)
the current study is the second step towards the overall objective of development of a clothing sizing system for Libyan children based on anthropometric body measurements of Libyan school children. The aim of this paper is to examine anthropometric measurements for students in grades four, five and six in the basic education stage, to collect body measurements of school children in Benghazi and analyze them using simple statistical methods that would help determining the body ranges and variations present for students in the three grades and use them, in turn, to develop sizing system of these grades. The anthropometric data were analyzed using Minitab program. ANOVA and kruskal-Wallis tests were used to identify differences between age groups. The results showed that there are differences between the most body measurements except the arm length and waist to hip length. These differences were taken into account when developing the sizing system. Pearson correlation coefficients analysis was carried out to determine the interrelationships between the various body measurements. From these findings it can be concluded that the weight is very strongly correlated with some dimensions. Height and weight measurements were used as a guide to determine the size of clothes. The mean values and the standard deviation were used for creating size steps for the size chart. Three kinds of sizes were identified: L (large), M (medium) and S (small).